Experimental and Numerical Study of Polypropylene/Polyethylene Thin Foil in Biaxial Tension. Issue 1 (October 2016) - Sguazzo, Carmen; Betz, Sebastian; Hartmann, Stefan
Abstract: The material under consideration is a thermoplastic copolymer blend of polypropylene and polyethylene (PP/PE), constituting the core layer of a steel/polymer/steel composite material. A biaxial loading machine was developed for studying the behavior of the copolymer subjected to in‐plane complex stress states. A study on the shape of the specimen by means of numerical finite element simulations and preliminary experimental tests are carried out, in order to obtain a maximization of the strain distribution in the middle region of the cruciform specimen. Afterwards, the sensitivity of the mechanical response under both equibiaxial and non‐equibiaxial conditions is addressed. All the experiments are monitored by means of a digital image correlation (DIC) system, providing full‐field measurements of the displacements, and, consequently, of the strain distribution. The presented experimental results will be used for validating the material model developed for the PP/PE layer material. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)